2022
DOI: 10.3390/polym14194169
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biodegradable Composites Using Polycaprolactone and Bamboo Powder

Abstract: The use of biodegradable polymers in daily life is increasing to reduce environmental hazards. In line with this, the present study aimed to develop a fully biodegradable polymer composite that was environmentally friendly and exhibited promising mechanical and thermal properties. Bamboo powder (BP)-reinforced polycaprolactone (PCL) composites were prepared using the solvent casting method. The influence of BP content on the morphology, wettability, and mechanical and thermal properties of the neat matrix was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…The thermal stability of both BTM‐CONT and BTM‐TAN were similar, reinforcing the FT‐IR data which suggested that addition of 1% tannin did not induce significant physicochemical changes in the BTM blends. An initial weight loss of ~2%–5% in both samples were observed below 200°C, which can be associated with the moisture and volatile compounds evaporation as reported early 39,42–44 …”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The thermal stability of both BTM‐CONT and BTM‐TAN were similar, reinforcing the FT‐IR data which suggested that addition of 1% tannin did not induce significant physicochemical changes in the BTM blends. An initial weight loss of ~2%–5% in both samples were observed below 200°C, which can be associated with the moisture and volatile compounds evaporation as reported early 39,42–44 …”
Section: Resultssupporting
confidence: 64%
“…An initial weight loss of $2%-5% in both samples were observed below 200 C, which can be associated with the moisture and volatile compounds evaporation as reported early. 39,[42][43][44] Before exposition to biodegradation, the thermal degradation of BTM occurred in two steps, with a smooth degradation peak at 240 C corresponding to a weight loss of around 15% and a strong degradation peak at 357 C with about 80% of weight loss. Conversely, materials submitted to the biodegradation process for 30 or 60 days showed only one thermal degradation step near 360 C, with weight losses around 85% (Figure 4a).…”
Section: Tga and Xrdmentioning
confidence: 99%
“…Besides, the hydrophilic behaviour of bambara nut shell ller upgrades the water uptake via appearance of hydrogen bonds between ller and water moieties. Then, increasing the Bambara nut ller loading increased the evolution of the hydrogen bond between ller and water moieties [45]. Many works of researchers reported that water absorption of natural bre/epoxy composite increases with an increase in ller loading [34,46].…”
Section: 11water Absorptionmentioning
confidence: 99%
“…Cellulose and its derivatives can also be used as additives or reagents in polymerization reactions to replace non-renewable chemicals and create bio-based materials [ 30 , 31 , 32 ]. Bio-based materials not only have the advantage of being cheaper because they exploit renewable resources, but also possess biodegradability and eco-compatibility characteristics [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%